Differential Effects of ACE Inhibitors and ARBs on Mortality in Patients with Hypertension - Vinall, Maria (MD Conference Express, 2013)
The primary goal of hypertension management is to reduce associated morbidity and mortality. This article discussed the differences in mortality and morbidity outcomes for angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs). Specific trials include ACCOMPLISH, ASCOT-BPLA, EUROPA, VALUE, VALIANT, ONTARGET, and ELITE II.